1985
DOI: 10.1016/0014-5793(85)80855-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mechanisms of modulation between rat liver cholesterol 7α‐hydroxylase and HMG‐CoA reductase

Abstract: The effects of microsomal HMG-CoA reductase kinase, cytosolic phosphoprotein phosphatase and cytosolic, thioldependent cholesterol 'la-hydroxylase stimulatory protein on purified cholesterol 7a-hydroxylase and HMG-CoA reductase from rat liver were compared. Neither HMG-CoA reductase kinase nor phosphoprotein phosphatase had any significant effect on cholesterol 7a-hydroxylase activity. They inhibited and stimulated, respectively, the activity of HMG-CoA reductase. The purified cytosolic protein which stimulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…These non-steroidal compounds are structurally and chemically unrelated to 7-dehydrocholesterol and show different physical properties, but are powerful inhibitors of 3␤-hydroxysterol ⌬ 7 -reductase in vivo and produce congenital anomalies similar to the Smith-Lemli-Opitz syndrome when fed to pregnant rats. (14,15). Both are more powerful inhibitors than the competitive inhibitors, ergosterol, 7-dehydrositosterol, and 7-dehydroepicholesterol [AY 9944 is 500 times more potent than BM 15.766; (I 50 ϭ 5 ϫ 10 Ϫ8 vs. 1 ϫ 10 Ϫ6 , respectively)].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These non-steroidal compounds are structurally and chemically unrelated to 7-dehydrocholesterol and show different physical properties, but are powerful inhibitors of 3␤-hydroxysterol ⌬ 7 -reductase in vivo and produce congenital anomalies similar to the Smith-Lemli-Opitz syndrome when fed to pregnant rats. (14,15). Both are more powerful inhibitors than the competitive inhibitors, ergosterol, 7-dehydrositosterol, and 7-dehydroepicholesterol [AY 9944 is 500 times more potent than BM 15.766; (I 50 ϭ 5 ϫ 10 Ϫ8 vs. 1 ϫ 10 Ϫ6 , respectively)].…”
Section: Resultsmentioning
confidence: 99%
“…The addition of Mg 2ϩ and ATP (phosphorylation) increased ⌬ 7 -reductase activity 2.5-fold. Thus, 3␤-hydroxysterol ⌬ 7 -reductase activity undergoes short-term regulation similar to cholesterol 7␣-hydroxylase ( 10), but opposite to HMG -CoA reductase, where dephosphorylation activates and phosphorylation inhibits enzyme activity (14).…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigations have indicated that cyp7a activity can be modified in vitro by phosphorylation-dephosphorylation processes (209,214,256,347,397,530,709,893,903,1093). Other investigators (60,274,578) have not obtained results consistent with this potential in vitro modulation of cyp7a activity, perhaps due to differences in experimental conditions (709). Whereas phosphorylation-dephosphorylation changes of the enzyme may modulate cyp7a in vitro, this author is unaware of any studies demonstrating the importance of such mechanisms in the control of cyp7a activity in intact cells or in vivo in animals.…”
Section: B Formation Of 7-oxygenated Sterolsmentioning
confidence: 99%
“…~~ by CAMP,^^,,^ or by insulin5s have been recorded and the evolution of the enzyme activity during embryonic development of the and differences in modulation mechanisms for the reductase and cholesterol 7a-mono-oxygenase have been traced. 58 Exogenously supplied mevalonate rapidly reduced the HMG-CoA reductase activity in a variety of tissues of plants and animals and thus inhibited the formation of steroids. In rat liver and in cultured hepatoma cells, mevalonate is believed to be the precursor of a product that decreases the level of reductase-specific mRNA.59*60 The identity of the presumed controlling compound is unknown, but candidates include cholesterol, ubiquinones, and isopentenyladenine (a component of several types of tRNA).…”
Section: Introductionmentioning
confidence: 99%